Effects of Choice of Work Tasks on On-Task, Aberrant, Happiness and Unhappiness Behaviours of Persons with Developmental Disabilities - Spevack, Sara (2004)
Effects of choice versus no choice of work tasks on work performance, inappropriate behaviours, happiness and unhappiness indices were examined in three studies. Study 1 examined the effects of a choice between a high and a low preference task, versus the assignment of the high preference task. Study 2 was similar to Study 1 except that the tasks in the choice condition were equally and moderately preferred. Study 3 was conducted by the participants’ instructors in their natural work settings. A total of five participants were involved across the three studies. Very few differences were found under the choice and no-choice conditions. More research is needed to examine the role of reinforcement history in establishing stimulus control effects of choice.